Korelasi Aktivitas Fisik dengan Lingkar Perut pada Dewasa Muda - Nurhasanah, Nurhasanah; Pardede, Imelda Tresia; Nauli, Feriyandi; Nasution, Fikri Roja; Hayati, Istiyana; Hermawan, Angga Rizki (Jurnal Ilmu Kedokteran, 2024)
Central obesity is a risk factor for various diseases. The prevalence of central obesity in the world continues to increase. One of the factors that can affect waist circumference is physical activity. The purpose of this study was to determine the correlation between physical activity and waist circumference in young adults. This was analytic study with cross sectional method. Data were taken using virtual interview questionnaires (International Physical Activity Questionnaire Long (IPAQ-L)) and direct waist circumference measurements, the research sample was 90 people obtained by purposive sampling technique. Spearman correlation test was performed to determine physical activity and waist circumference in young adults. The results showed that the highest average physical activity was at the age of 20 years, namely 5332.35 MET-minutes per week and for males, namely 5199.21 MET-minutes per week. The highest average waist circumference was at the age of 19 years, namely 87.38±14.14 cm and for males, namely 92±14.68 cm. There is a significant negative correlation between physical activity and waist circumference in young adults (p = 0.0001) with a strong correlation (r = -0.714).